The Effect of Mastery of Diction and Language Style on the Ability to Write Buginese Poetry in Class X IPA II SMA Negeri 9 Wajo - Lisa Syari Sahrang; Johar Amir; Azis Azis (Universitas Negeri Makassar, 2021)
The Effect of Mastery of Diction and Language Style on the Ability to Write Buginese Poetry in Class X IPA II SMA Negeri 9 Wajo.This research is a pre-experimental study that aims to describe the influence of diction and language style mastery on the ability to write Bugis poetry in class X IPA II SMA Negeri 9 Wajo. The independent variable in this study is the mastery of diction and language style, while the dependent variable is writing Bugis poetry. The population in this study were 30 students of class X IPA II SMA Negeri 9 Wajo. The data analysis technique is descriptive statistical analysis and inferential analysis. Based on the results of the study, it shows that (1) The mastery of diction of class X IPA II SMA Negeri 9 Wajo obtained an average score of 78.26 in the medium category (2) Mastery of the language style of class X IPA II SMA Negeri 9 Wajo obtained an average score 79.14 with the moderate category, (3) there is a significant influence between the mastery of diction and language style on the ability to write Bugis poetry in class X IPA II SMA Negeri 9 Wajo because the significance value of diction mastery is 0.481 and the value of language style mastery is 0.161, which means the significance value greater than α 0.05.Keywords: Influence, Diction and Language Style, Writing Bugis Poetry.Abstrak: Pengaruh Penguasaan Diksi dan Gaya Bahasa Terhadap Kemampuan Menulis Puisi Bugis Siswa Kelas X IPA II SMA Negeri 9 Wajo. Penelitian ini adalah penelitian pra eksperimen yang bertujuan untuk mendeksripsikan ada tidaknya pengaruh penguasaan diksi dan gaya bahasa terhadap keampuan menulis puisi Bugis siswa kelas X IPA II SMA Negeri 9 Wajo. Variabel bebas dalam penelitian ini adalah penguasaan diksi dan gaya bahasa sedangkan veriabel terikatnya adalah menulis puisi Bugis. Populasi dalam penelitian ini adalah siswa kelas X IPA II SMA Negeri 9 Wajo sebanyak 30 siswa. Teknik analisis data yaitu dengan analisis statistik deskriptif dan analisis inferensial. Berdasarkan hasil penelitian menunujukkan bahwa (1) Penguasaan diksi siswa kelas X IPA II SMA Negeri 9 Wajo memperoleh nilai rata-rata 78,26 dengan kategori sedang (2) Penguasaan gaya bahasa siswa kelas X IPA II SMA Negeri 9 Wajo memperoleh nilai rata-rata 79,14 dengan kategori sedang, (3) terdapat pengaruh yang signifikan antara penguasaan diksi dan gaya bahasa terhadap kemampuan menulis puisi Bugis siswa kelas X IPA II SMA Negeri 9 Wajo karena diperoleh nilai signifikasi penguasaan diksi 0.481 dan nilai penguasaan gaya bahasa 0.161 artinya nilai signifikansi lebih besar dari α 0.05.